Randomised controlled trial of referral to a telephone-based weight management and healthy lifestyle programme for patients with knee osteoarthritis who are overweight or obese: a study protocol. Issue 3 (3rd March 2016) - O'Brien, Kate M; Wiggers, John; Williams, Amanda; Campbell, Elizabeth; Wolfenden, Luke; Yoong, Serene; Robson, Emma K; McAuley, James; Haskins, Robin; Kamper, Steven J; Williams, Christopher
Abstract : Introduction: Knee osteoarthritis (OA) is one of the most common chronic diseases worldwide and is associated with significant pain and disability. Clinical practice guidelines consistently recommend weight management as a core aspect of care for overweight and obese patients with knee OA; however, provision of such care is suboptimal. Telephone-based interventions offer a novel approach to delivery of weight management care in these patients. The aim of the proposed study is to assess the effectiveness of referral to a telephone-based weight management and healthy lifestyle programme, previously shown to be effective in changing weight, in improving knee pain intensity in overweight or obese patients with knee OA, compared to usual care. Methods and analysis: A parallel, randomised controlled trial will be undertaken. Patients with OA of the knee who are waiting for an outpatient orthopaedic consultation at a tertiary referral public hospital within New South Wales, Australia, will be allocated to either an intervention or a control group (1:1 ratio). After baseline data collection, patients in the intervention group will receive a 6-month telephone-based intervention, and patients in the control group will continue with usual care. Surveys will be conducted at baseline, 6 and 26 weeks post-randomisation. The study requires 60 participants per group to detect a two-point difference in pain intensity (primary outcome) 26 weeks after baseline. Ethics and dissemination: The study is approved by the Hunter New England Health Human Research Ethics Committee (13/12/11/5.18) and the University of Newcastle Human Research Ethics Committee (H-2015-0043). The results will be disseminated in peer-reviewed journals and at scientific conferences. Trial registration number: ACTRN12615000490572, Pre-results.